Factors Influencing Choice of Energy Sources in Rural Pakistan (The Pakistan Development Review, 2016)
Modernisation of the agricultural and industrial sectors in Pakistan over the last thirty years, increased village electrification, increasing use of energy appliances by domestic users, and the usage of modern technology in all sectors, caused energy demand to increase more rapidly than energy supply. Sources of energy vary between urban and rural populations, across income groups, and by type of households. Pakistanis consume energy from both modern and traditional sources for different purposes, such as lighting, cooking, heating, and transportation. Modern sources of energy include electricity, oil, gas and coal, while traditional sources consist of animal/plant residue (firewood, crop residue and animal waste). Using a multinomial logit regression model, this study analyses how rural households make choices among different energy alternatives. The results suggest that because of the limited access to modern energy sources, households rely on traditional sources excessively, which may have a negative impact not only on human and animal health but also on the environment. These results suggest that the conversion of traditional energy sources into modern ones, such as, biogas, use of energy efficient appliances, etc. can have a positive impact on the environment and sustainable economic growth. JEL Classification: R20, D11, Q43, Q42, Q5 Keywords: Rural, Households, Energy Consumption, Energy Sources, Environment